1994
DOI: 10.1086/646839
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epidemic and Endemic Isolates of Xanthomonas maltophilia by Contour-Clamped Homogeneous Electric Field Gel Electrophoresis

Abstract: Although it is a convenient and economical tool, the antibiogram has limitations. Analysis by CHEF should help to elucidate the epidemiological spread of X maltophilia in the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…6,15,21,[25][26][27] In our study, the heterogeneity of the S. maltophilia strain types documented by pulsed-field gel electrophoresis of nine isolates suggested that the organisms came from multiple sources.…”
Section: Discussionmentioning
confidence: 49%
“…6,15,21,[25][26][27] In our study, the heterogeneity of the S. maltophilia strain types documented by pulsed-field gel electrophoresis of nine isolates suggested that the organisms came from multiple sources.…”
Section: Discussionmentioning
confidence: 49%
“…and Citrobacter spp., and 5 to 60 s for 22 h for Serratia spp. (3,8,9,13). The gels were stained with ethidium bromide and photographed under UV light.…”
Section: Methodsmentioning
confidence: 99%
“…Although not the first evidence of nosocomial cross-transmission of this microorganism, the authors' use of molecular methods was thorough and contributed to what is known about this important organism. We used the molecular techniques contour-clamped homogeneous electric-field gel electrophoresis 2 and arbitrarily primed polymerase chain reaction 3 to compare 64 hospital endemic and neonatal intensive care unit epidemic isolates of S maltophilia. Additionally, we conducted a retrospective chart review to determine risk factors.…”
Section: To the Editormentioning
confidence: 99%
“…We showed antibiograms to have a Simpson's Discriminatory Index of 0.87 when applied to 56 isolates of S maltophilia. 2 Although analyzing variability in antibiograms becomes extremely complicated when multiple strains are involved, a single pair can often be analyzed efficiently and economically. The data may help a bedside clinician motivate others to expend resources constructively to prevent further infections.…”
Section: To the Editormentioning
confidence: 99%